Businessmen in arms how the military and other armed groups profit in the MENA region - Grawert, Elke; Abul-Magd, Zeinab (Rowman & Littlefield Publishers, 2016)
This collection of essays from international experts examines the economic interests of armed actors ranging from military businesses in Egypt, Turkey, Iran, Pakistan, Jordan, Sudan, and Yemen to retired military officers' economic endeavors and the web of funding of non-state armed groups in Syria and Libya. Control of businesses producing both military and civilian goods, retention of financial, material, or military support, and allocation of lucrative administrative or political positions to armed actors appear to be entrenched economic pillars of the military power in the region.